Raising the bar: Exercise recommendations for pregnant athletes - Davenport, M. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
Over the last decade, elite athletes have begun to challenge stereotypes regarding participation in performance sport during pregnancy. From marathon runner Paula Radcliffe to tennis star Serena Williams, and most recently sprinter Allyson Felix, female athletes are pushing back against the societal narrative that they should "take it easy" during pregnancy. Although extensive literature supports the safety and benefits of prenatal exercise, these data are primarily limited to the general obstetric population. Current exercise guidelines outline 150 minutes of moderate-intensity physical activity each week. However, these conservative recommendations do not serve elite athletes who substantially exceed this advice during training. Several studies demonstrate that sport and exercise participation declines in pregnant athletes due, at least in part, to a lack of research and policy in this area. Pregnancy is a period of profound physiological and psychological adaptation to support the growing foetus. Although early recommendations cautioned against exercise during pregnancy, over the last decade we have had a transformational shift in our view of physical activity and exercise away from an activity that is "nice to do" to a prescription for enhanced health for both mother and baby. Yet, prenatal exercise is fraught with numerous myths and misconceptions, especially for recreational and elite athletes. In this lecture, Dr. Davenport will provide an overview of current global guidelines for prenatal exercise (including recommendations, screening tools and contraindications to exercise), and describe how physiological adaptations to pregnancy impact exercise prescription. She will also present novel data and considerations specific to the pregnant athlete, including heavy weightlifting, HIIT, Valsalva and supine exercise. This lecture will be designed to be relevant to the practitioner and researcher, as well as coaches and athletes.